(3QSGdI aj GdYQhVs ((3eMeO Hf edc GdMGQKi s)
(3ChdgG (B:s
(3jHOC HHGH GdZjhH hGdbhGai s
(3BNQgG (B:s
(3GdCUd ai GdTQM ai GdaJM hGdMeO ddg GdhGLH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs